Splenectomy-Induced Leukocytosis Promotes Intratumoral Accumulation of Myeloid-Derived Suppressor Cells, Angiogenesis and Metastasis. (3rd October 2017) - Sevmis, Murat; Yoyen-Ermis, Digdem; Aydin, Cisel; Bilgic, Elif; Korkusuz, Petek; Uner, Aysegul; Hamaloglu, Erhan; Esendagli, Gunes; Karakoc, Derya
ABSTRACT: Background : Enlargement of the spleen is commonly observed in animal models of cancer. Here, in a breast cancer model, it was aimed to determine the effect of splenectomy on circulating and tumor-infiltrating myeloid-derived suppressor cells (MDSCs), tumor angiogenesis, and metastasis. Methods : Mice were inoculated with 4T1 breast cancer cells and underwent splenectomy or sham laparotomy. Tumor growth and survival of animals were followed. Macroscopic and histopathological analyses were performed to determine splenomegaly and metastasis. Immunophenotyping of myeloid cells was performed with flow cytometric analysis of CD11b, Gr-1, F4/80, CD206, CD11c, and F4/80 markers. Suppressive function of MDSCs on T cell proliferation was studied in cocultures. Tumor angiogenesis and granulocytic myeloid cell infiltration in the metastatic foci were studied by CD31 and Ly6G immunohistochemistry, respectively. Results : The mice bearing breast tumors underwent total splenectomy at an early time point of tumorigenesis when only low levels of MDSCs had accumulated in the spleen. Circulating and tumor-infiltrating MDSCs, and tumor-associated macrophages (TAMs) were increased following splenectomy. Nevertheless, splenectomy could only lead to a temporary deceleration in tumor growth but favored lung metastasis and angiogenesis in the long run. Conclusion : Our data demonstrated a link among splenectomy-induced leukocytosis, accumulation of circulating and tumor-infiltrating MDSC, and enhanced angiogenesis and metastasis. Therefore, as a part of oncological surgery, favorable and unfavorable facets of the splenectomy must be considered to improve therapeutic efficacy.